The Existence of Totammaq Tradition Celebration in Mandar Culture Mandar Community, West Sulawesi - Arifin, Iqbal; Darmayanti, Dyan Paramitha (Universitas Negeri Makassar, 2023)
This study investigates the diversity and difficulties associated with the Totammaq Tradition Celebration in Mandar communities in West Sulawesi. The impact of globalization, social change and internal dynamics on the existence of Totammaq is understood through a qualitative case study. A total of nine informants were purposively selected to represent different ages, genders and roles in society. The main focus of this research is the transformation of cultural values and globalization, illustrating how global information flows and changes in community beliefs can affect Totammaq operations. To gain a more in-depth understanding of Totammaq's role in the cultural identity of the Mandar people, data analysis was conducted through participant observation involved in the celebration and document examination. The results showed that both internal factors, such as the role of the younger generation and community dynamics, and external factors, such as changes in global cultural values, have a major influence on the sustainability of Totammaq. In addition, government and cultural policies play an important role in keeping the tradition alive. Amidst the challenges of the times, innovation and adoption appear to be effective strategies to maintain Totammaq's sustainability. Therefore, this research not only provides an in-depth picture of how the Totammaq lived, but also asks critical questions about how the Mandar people can maintain their traditions today. This research can help in cultural preservation in West Sulawesi and similar regions.